Entre máscaras e rostos: um estudo sobre Boa Noite Punpun - Fontenele, Amanda Venancio (2023)
Considering the face as a fundamental interface in human relations and life in society and that, in order to exist, a face needs to interact with other faces, we reflect in this work on the face in the development of the manga Boa Noite Punpun, especially in the construction and development of the protagonist, a character whose face, even if not completely revealed, shows many faces. Based on Belting's iconology, which considers image, body and media as an inseparable triad, and the narrative structure of comics, a mostly imagetic media, we question in this work how the images of the face – and faces – of Punpun happen and how the reader can participate in this process. To fulfill this task, a bibliographical review of the studies related to the comic and the analysis of the images of the main character based on the scientific fields of image and face study was chosen as a methodology, dialoguing with studies in comics. The main objective was to propose a reflection on how the face, faces and masks communicate through the act of showing and hiding, and how the reading of Boa Noite Punpun can highlight this process. Keywords: face; faces; masks; mango; good night Punpun.